DASHBOARD UNTUK MONITORING DAN EVALUASI PRESTASI SISWA SMA BERBASIS KURIKULUM 2013 (Information Technology and Telematics, 2015)
Abstrac Curriculum 2013 is a curriculum that promotes the understanding, skills and character education, students are required to understand the above materials, active in the presentations and discussions as well as having good manners high discipline, this curriculum is a continuation of Competency-Based Curriculum (CBC) 2004. The Dashboard is made to see the development of high school students study in accordance with the National Curriculum in 2013, which takes a case study at the School MA Darul Ulum Bandungharjo. The purpose of this dashboard design is as a media presentation of key information using graphs, as well as the assessment of data processing. In the assessment data has three components of the assessment, the value component of attitude, knowledge and skills. Where the results will be used to assist and facilitate the school in making decisions related to the results of the students' school. This dashboard using Prototyping (Prototype), with tools / aids system development using UML (Unified Modeling Language). This dashboard development using PHP with MySQL database. Keywords: Dashboard, Prototyping, PHP, MySQL, Monitoring, Curriculum 2013.